Pengaruh Pelatihan Komunikasi ISOBAR (Identify, Situation, Observations, Background, Assesment, Recommendation) Terhadap Pengetahuan dan Kualitas Pelaksanaan Timbang terima di RSUD Padang Pariaman : Effect of ISOBAR Communication Training (Identify, Situation, Observations, Background, Assessment, Recommendation) on Knowledge and Quality of Weigh-In Implementation at Padang Pariaman Hospital - Candra Deni Mairosa; Rizanda Machmud; Jafril (NERS Jurnal Keperawatan, 2019)
Handover communication is the transfer of information related to the patient for the continuity of care provided. Errors in the transfer of patient information can result in negligence of treatment, inadequate care and death, for this reason a communication framework is needed so that the information conveyed is fast, precise and accurate. ISOBAR is an operative communication framework that is more structured, complete and accurate so that it can support patient safety. This study aims to identify the effect of ISOBAR communication training for the knowledge and quality of handover in Padang Pariaman District Hospital. This research used a quasy experimental Pre-Post Test with Control Group design. The technique of taking samples was systematic random sampling. The sample in this study was the team leader and the person in charge of the shift with a total of 23 intervention groups and 18 control groups. Data collection is done by questionnaire and observation. Analysis of the data used is the Mann-Whitney statistical test to see differences in the intervention and control groups. The results of this study prove that there is an influence of ISOBAR communication training on knowledge (p = 0,000) and the quality of handover (p = 0,000) in the intervention group. It is expected that the Hospital can use ISOBAR communication in handover to improve the quality of human resources and make policies regarding the application of ISOBAR communication in an effort to improve patient safety.